The Internet of Everything. Advances, Challenges and Applications - Shinde, Gitanjali (De Gruyter Series on the Internet of Things, 2019)
The phenomenon of Internet of Things (IoT) and the concept of Internet of Everything (IoE) respond to the need for machine to machine communication, automation, smart computing and ubiquitous access to personal devices. This book aims to present different aspects of IoE, challenges faced by IoE and its applications.